2019
DOI: 10.1037/amp0000460
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting theory on research use: Turning to policymakers for fresh insights.

Abstract: Social science has done well in providing empirical studies that depict how research is used in policymaking. Yet it performs less well in another contribution science can make-developing explanatory theoretical frameworks that predict and promote future research use. To address this theoretical void, onsite studies of policymakers have been called for. In this qualitative study, semistructured, face-to-face interviews were conducted with 123 legislators in 2 states, 32 legislators nominated by colleagues as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…A fourth friction is how policymakers influence the attitudes and beliefs of others. The most frequent use of research reported in our study was for argumentation—to persuade others to support one's view or to anticipate and to counter an opposing view (Bogenschneider et al, ). Academics look askance when research is used, not for forming opinions, but for supporting arguments, particularly for a preexisting position (Weiss, ); this dismissive reaction disregards the importance of persuasion in a governing process that privileges compromise and consensus building over brute force (Albaek, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A fourth friction is how policymakers influence the attitudes and beliefs of others. The most frequent use of research reported in our study was for argumentation—to persuade others to support one's view or to anticipate and to counter an opposing view (Bogenschneider et al, ). Academics look askance when research is used, not for forming opinions, but for supporting arguments, particularly for a preexisting position (Weiss, ); this dismissive reaction disregards the importance of persuasion in a governing process that privileges compromise and consensus building over brute force (Albaek, ).…”
Section: Discussionmentioning
confidence: 97%
“…In our study, persuasion was the primary way policymakers used research (Bogenschneider, Day, & Parrott, ). Legislators acknowledged, however, that persuasion occurs, not in isolation, but in combination with relationships: “I think the intersection of policy and politics is that you don't get your policy enacted unless you can convince people—and research helps convince them.”…”
Section: Institutional Culture Of State Legislatures: Operational Pramentioning
confidence: 99%
“…This is particularly true for interventions that address contentious policy topic areas, where politicization often sidetracks evidence-based decision-making (Head, 2010). Research often gets used in the policymaking process to build support from others for policy priorities (Bogenschneider et al , 2019b) in legislatures and in non-partisan policy settings. In the education sphere, for example, research by Penuel and colleagues (2018) found that school district leaders turned to research in part to foster buy-in for initiatives they were implementing.…”
Section: What We Know About Evidence and The Policy Decision-making Pmentioning
confidence: 99%
“…This commentary will discuss two key challenges for the model. First, research studying the integration of evidence into policymaking points to a complex set of factors influencing implementation decisions, including leadership, maintaining relationships, windows where policies can advance, financial resources and availability and campaign promises (Kingdon, 1995; National Research Council, 2012; Oliver et al , 2014; Cairney et al , 2016; Bogenschneider, Corbett & Parrot, 2019a, 2019b; Nutley et al , 2019). These factors complicate the model's recommendations, which rely primarily on making decisions about selecting and implementing evidence-based programs based on findings from research.…”
mentioning
confidence: 99%
“…Além do uso de processo, também foi identificado em apenas um dos grupos o impacto simbólico, conforme comentado anteriormente, no sentido de dar maior credibilidade aos achados das pesquisas realizadas pelo grupo. Em se tratando de impacto em políticas públicas, esperava-se, com base na literatura analisada, que esse tipo de impacto fosse mais presente (Bogenschneider et al, 2019;Williamson et al, 2019). Entretanto, ressalta-se que os entrevistados da comunidade de políticas públicas atuam em cargos menos estratégicos e políticos (onde esse impacto provavelmente seria mais presente) e, possivelmente em virtude desse perfil, essa categoria de impacto foi menos relevante.…”
Section: Disucssão Dos Resultadosunclassified